ALQURAN DAN RAHASIA ANGKA: Kajian Kitab Tafsir Karya Abu Zahra al-Najdi - Muhammad Akrom Adabi (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2019)
The studies of miracles of the Qur’an have long been dominated by the composition of the versatility, the selection of discussions and the placement of balanced vocabulary, all of which extinguish the miracles of the Qur’an language. The studies continue to develop and emerge the studies of miracles of the Qur’an by looking at the mathematical miracles in the Qur’an. The miracles in the Qur’an were first introduced by Rashad Khalif by discovering the miracles of numbers in Qur’an verses. Some other studies tried to reveal the miracles of the Qur'an through matching and shifting certain aspects in Qur'an. Unlike in the previous studies, Abu Zahra An-Najd tried to relate words with the phenomenon of mathematical miracles that had been studied previously. This study tries to amend I‘jāz ‘adadī in the Qur'an and the Secret Book of Abu Zahra an-Najdi.